The effect of altitude on turbocharger performance parameters for heavy duty diesel engines: experiments and GT-Power modeling - Thompson, Andrew T., author; Marchese, Anthony J., advisor; Olsen, Daniel, committee member; De Miranda, Michael A., committee member (Colorado State University. Libraries, 2014)
Operation at high altitude increases the risk of high cycle fatigue (HCF) failure on turbine blades in internal combustion engine turbochargers. Because engine manufacturers rarely acquire performance data at the high altitude limits of their engines, it is imperative that manufacturers rely on computer simulation to visualize, quantify and understand turbocharger performance when experimental tests are not practical. Typically, CFD and FEA models are used to predict HCF damage for turbine wheels. However, the boundary conditions and other input data required for such simulations are often unknown at high altitudes. The main objective of this thesis was to develop these critical boundary conditions and input data for a Cummins QSK19 CI engine and a Cummins QSK50 CI engine. This objective was accomplished by installing and testing both of these engines at 5000ft elevation and calibrating GT-Power computer simulation models against the experimental data at 5000ft elevation. After the models were calibrated against experimental data, the models were extrapolated to the altitude capability of these engines and the critical boundary conditions were recorded. In addition to the diesel engine experiments and modeling, a single cylinder HCCI computer simulation model was developed to evaluate the performance of Woschni and Hohenberg heat transfer correlations by comparing GT-Power model predictions with measured in-cylinder pressure data. Analysis was performed by generating a single zone GT-Power model of a modified John Deere DI 2.4L four-cylinder engine, which was previously converted at CSU to operate in HCCI port injection mode. The HCCI engine was operated at an equivalence ratio of 0.33 and a fuel mixture of 40% iso-octane and 60% n-heptane by volume. The combustion chemistry was modeled using a reduced Primary Reference Fuel (PRF) mechanism from Ra and Reitz with 41 species and 130 reactions. The Cummins modeling results indicate that GT-Power can predict turbocharger performance within 7.59% variation from measured data at 5000ft. When the model was extrapolated to 8000ft, GT-Power predicted an average expansion ratio increase of 1.81% and an average turbine inlet temperature decrease of 2% for the QSK19 CI engine. The Cummins QSK50 GT-Power model predicted an average expansion ratio increase of 2.73% and an average turbine inlet temperature decrease of 9.12% from 5000ft to 8000ft. The HCCI simulation results showed that GT-Power can accurately predict the start of combustion. In addition, the simulation results showed that the pressure rise rate has a low sensitivity to the in-cylinder heat transfer rate.
Keywords: HCCI; altitude; engines; GT-Power; modeling; turbocharger